The SV40 72 base repair repeat has a striking effect on gene expression both in SV40 and other chimeric recombinants. - Moreau, P (1981)
By introduction of recombinant plasmids into monkey CV1 cells, we have unambiguously demonstrated that sequences entirely within the 72 bp repeat, which is located upstream of the SV40 early region, are crucial for T-antigen expression in vivo. We have also shown that a DNA fragment containing the 72 bp repeat, inserted directly before chicken conalbumin or adenovirus-2 major late promoter sequences in chimeric plasmids where these promoters replace that of the SV40 early genes, caused a dramatic increase in the expression of T-antigen in vivo. This effect was independent of the orientation of the 72 bp repeat, but was sensitive to its location within the plasmid, when the 72 bp repeat was separated from the promoter sequences, T-antigen expression was reduced. Insertion of the 72 bp repeat into equivalent plasmids containing no known eukaryotic promoter sequences (plasmids which were not detectably expressed in vivo) gave rise to a measurable, but smaller level of expression. The stimulation of expression by the 72 bp repeat is cis-acting : it required covalent linkage to the recombinant. We discuss the possibility that the 72 bp repeat region in SV40 may act as a bi-directional entry site for RNA polymerase B such that promoter sequences linked to the repeat are more efficiently utilised.